SEMANTIC RECONSTRUCTION OF QUR’ANIC VALUES FOR MULTICULTURAL EDUCATION - Nasarudin; Abdul Aziz; Muhamad Arfan; Muhammad Zakki Masykur; Kartika Ratnasari (Khazanah: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to reconstruct the meaning of multicultural education in the Qurâ€™an through Toshihiko Izutsuâ€™s semantic epistemology and to examine its implications for global ethical principles. Using a descriptive-analytical library research design, the study demonstrates that Izutsuâ€™s semantic framework, comprising the identification of key concepts, basic meanings, relational meanings, historical meanings, and the Qurâ€™anic Weltanschauung, is highly relevant for uncovering the Qurâ€™anâ€™s vision of multiculturalism. The analysis shows that key terms such as syuÊ¿Å«ban, qabÄÊ¾ila, alsinatikum, and alwÄnikum are interconnected within a complex semantic network. This interconnection reveals a universal semantic transformation in which these terms shift from narrow pre-Qurâ€™anic connotations to an inclusive worldview that regards ethnic, linguistic, and racial diversity as signs of divine greatness and as foundations for strengthening human relationships (li-taÊ¿ÄrafÅ«), rather than as sources of division. The reconstruction of the Qurâ€™anâ€™s internal semantic network ultimately forms a worldview grounded in equality, dignity, and human brotherhood, where moral worth is determined by piety rather than physical or social identity. The findings further highlight that principles such as tolerance, justice, equality, and humanity emerge as inseparable components of the Qurâ€™anic Weltanschauung, offering a strong philosophical basis for multicultural education rooted in sacred text and oriented toward collective well-being